Crianças e adolescentes em situação de violência sexual: a realidade de um serviço público de referência no Brasil - Nakamura, Bianca (2024)
This study aimed to describe the sociodemographic characteristics of children and adolescents cared for in a specialized service for victims of sexual violence and the organizational particularities and access to this public health service in a context of a global pandemic. This is a descriptive study with a quantitative approach carried out retrospectively based on the reading of the electronic medical records of children and adolescents, aged 0 to 14 years, victims of sexual violence, assisted in 2020. The variables were analyzed and compared according to the victim's gender, bond with the aggressor and access to specialized services. Girls were the majority (84.3%) of the victims assisted, 50.7% were black and brown. In most cases, the aggressors were known to the victims (60.2%). Of the victims treated in the emergency room, 25.0% did not follow up with the specialized service. These results demonstrate the reflection of a patriarchal structurein our country, which portrays gender inequality. Girls who suffer sexual violence live in a context in which they are doubly violated and made invisible, because they are girls and because they are black. The lower number of reports and requests by boys for protection services may also be due to this structure, which reinforces greater silencing of victims in the face of the embarrassment caused by the sexual violence suffered. Our results also highlight some challenging aspects in guaranteeing access for victims of sexual violence to a public health service.